PENGARUH SENAM PROLANIS TERHADAP PENURUNAN KADAR GULA DARAH PADA LANSIA DI PUSKESMAS DOLAT RAYAT KABUPATEN KARO TAHUN 2020 - Rentawati Purba; Adi Arianto (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Abstract In Indonesia, diabetes mellitus continues to show a significant increase in cases each year.The development of various degenerative diseases are currently very rapidly. Degenerative diseases are usually referred to diseases that accompany the aging process.Blood sugar levels are a form of carbohydrate metabolism that serves as the main energy source is isontrolled by insulin. Diabetes occurs due to increased blood sugar levels or hyperglycemia due to insulin deficiency. The World Health Organization (WHO) states that cases of diabetes mellitus in 2015 reached 415 million cases of adults with diabetes. It is due to never stretching joint muscles such as aerobic exercise or jogging, it is necessary to do prolanis gymnastics.The purpose of this study was to identify the effect of prolanis exercise on reducing blood sugar levels in the elderly at the DolatRayat Health Center in Karo District. The type of research is a pre-experimental design with pre and post test one group design. The population of this study was 40 people. The number of samples in this study were 40 people with saturated sample techniques (total sampling). Data were analyzed by using paired sample t-test. The results showed that there was an effect of Prolanis exercises on reducing blood sugar levels in the elderly at the Dolat Rayat Health Center in Karo District, where a p-value obtained 0.000 <0.05. Therefore, it is expected that the results of the research can be additional information for Public Health Centre and related institutions to continue promoting this program.